Hemolacria in severe Migraine – Case report - Thapa, Dinesh Kumar; Prasai, Ashma; Yadav, Niraj (Eastern Green Neurosurgery, 2022)
Bloody tears or hemolacria mostly occurs in bleeding disorders, infections, and malignant condition of the eyes and surrounding structure. It is very rare to have it in migraine headache. Hereby, we report a case of Hemolacria in a 47 years lady during acute attack of migraine.